Restriction And Classification Of Unmanned Aerial Vehicles In War According To The Principles Of International Law - Mohamad Akib Ismail (Estudiante Law Journal, 2020)
This research aims to find out how international law exists in the assessment and limits the company of Unmanned Aerial Vehicles (UAVs) in war from international legal principles and provides an overview of the classification of UAVs as weapons based on existing regulations. By regulations and international legal products that are the limiting parameters of UAVs such as St. Petersburg 1868, The Hague Convention 1907 and also pay attention to the foresight regarding the classification of UAVs themselves. The research method used is the juridical normative legal research method. The problem in this article is how to limit the use of UAVs in the war based on the principles of international law and knowing how to classify UAV classes as weapons in battle according to international law. Based on the research results on the use and classification of UAVs in the world of firearms, it is still far from clear. It has not been able to provide "safety" parameters clearly and unequivocally in international legal products. The use of UAVs as weapons is still relatively new. Researchers categorize UAVs now better known as the AWS category. The use of which will be limited by the principles of international law.